(untitled) (The Journal of Interdisciplinary Human Studies, 2025)
This article examines the legal methodology of Burhan al-Din al-Marghinani (1135–1197) through a comparative analysis with major Hanafi jurists, including Abu Hanifa, Abu Yusuf, Muḥammad al-Shaybani, and al-Sarakh si. By analyzing primary texts and classical commentaries, the study identifies methodological continuities and evolutions within the Hanafi legal tradition, demonstrating how Marghinani synthesized and systematized centuries of juristic reasoning into a coherent legal framework.